2003
DOI: 10.1016/j.newar.2003.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Status of CMB polarization measurements from DASI and other experiments

Abstract: We review the current status and future plans for polarization measurements of the cosmic microwave background radiation, as well as the cosmology these measurements will address. After a long period of increasingly sensitive upper limits, the DASI experiment has detected the E -mode polarization and both the DASI and WMAP experiments have detected the TE correlation. These detections provide confirmation of the standard model of adiabatic primordial density fluctuations consistent with inflationary models. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Studies of the cosmic microwave background (CMB) have dramatically progressed over the past two decades (e.g., Smoot et al 1992;Cheng et al 1997;Baker et al 1999;Miller et al 1999;de Bernardis et al 2000;Knox & Page 2000;Hanany et al 2000;Lee et al 2001;Romeo et al 2001;Netterfield et al 2002;Halverson et al 2002;Kovac et al 2002;Carlstrom et al 2003;Pearson et al 2003;Scott et al 2003;Benoît et al 2003;Spergel et al 2003;Johnson et al 2007;Chiang et al 2010). The current ΛCDM cosmological model provides an excellent fit to the CMB data across a wide range of angular scales, and is supported by complementary observations of large scale structure (e.g., Reid et al 2012;Ho et al 2012), Baryon Acoustic Oscillations (BAO e.g., Blake et al 2011;Anderson et al 2012;Busca et al 2013), Type Ia supernovae (e.g., Hicken et al 2009;Kessler et al 2009;Conley et al 2011), galaxy cluster measurements (e.g., Vikhlinin et al 2009;Mantz et al 2010;Rozo et al 2010;Tinker et al 2012) and observations of gravitational lensing (e.g., Massey et al 2007;Fu et al 2008;Schrabback et al 2010;Suyu et al 2010;Heymans et al 2012;Kilbinger et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the cosmic microwave background (CMB) have dramatically progressed over the past two decades (e.g., Smoot et al 1992;Cheng et al 1997;Baker et al 1999;Miller et al 1999;de Bernardis et al 2000;Knox & Page 2000;Hanany et al 2000;Lee et al 2001;Romeo et al 2001;Netterfield et al 2002;Halverson et al 2002;Kovac et al 2002;Carlstrom et al 2003;Pearson et al 2003;Scott et al 2003;Benoît et al 2003;Spergel et al 2003;Johnson et al 2007;Chiang et al 2010). The current ΛCDM cosmological model provides an excellent fit to the CMB data across a wide range of angular scales, and is supported by complementary observations of large scale structure (e.g., Reid et al 2012;Ho et al 2012), Baryon Acoustic Oscillations (BAO e.g., Blake et al 2011;Anderson et al 2012;Busca et al 2013), Type Ia supernovae (e.g., Hicken et al 2009;Kessler et al 2009;Conley et al 2011), galaxy cluster measurements (e.g., Vikhlinin et al 2009;Mantz et al 2010;Rozo et al 2010;Tinker et al 2012) and observations of gravitational lensing (e.g., Massey et al 2007;Fu et al 2008;Schrabback et al 2010;Suyu et al 2010;Heymans et al 2012;Kilbinger et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For ground based observations the window channels at 40, 90 and 140 GHz are optimum due to the low atmospheric attenuation at these frequencies. To this date the 40 and 90 GHz channels have been used in several LNA based experiments [7], however, the LNA technology has not been sufficiently low noise at 140 GHz range. Thus, by adding the 140 GHz LNA capability the complete CMB measurement can be carried out using cryogenically cooled (T=20 K) InP MMIC LNAs.…”
Section: Cosmic Microwave Background Imagersmentioning
confidence: 99%
“…By comparing the measured CMB power spectra with theoretical predictions, the WMAP team determined the cosmological parameters with a few percent precision (Spergel et al , 2007Komatsu et al 2009Komatsu et al , 2011, and found that the observed CMB fluctuations are consistent with predictions of the concordance ΛCDM model with scaleinvariant adiabatic fluctuations generated during the inflationary epoch Peiris et al 2003;Komatsu et al 2011). Recent ground-based and balloon-borne experiments that have performed CMB power spectrum measurement and cosmological parameter estimation include the South Pole Telescope (SPT; Keisler et al 2011), the QUaD experiment (Brown et al 2009), the Arcminute Cosmology Bolometer Array Receiver (ACBAR; Reichardt et al 2009), the Cosmic Background Imager (CBI; Mason et al 2003), the Atacama Cosmology Telescope (ACT; Fowler et al 2010), the Degree Angular Scale Interferometer (DASI; Carlstrom et al 2003), BOOMERANG (Jones et al 2006), Archeops (Benoît et al 2003), and MAXIMA (Lee et al 2001).…”
Section: Introductionmentioning
confidence: 99%